El hombre y la naturaleza en testimonios epigráficos de la Grecia Antigua.Un abordaje desde la Lingüística (Iter, 2022)
As Kwiatkowska (2001:15) points out throughout history, man has always hada particular relationship, more or less close, with nature; and that relationshipmanifests itself both in their way of thinking or speaking, and in their behavior. Just as the paintings, the poems, the varied literary, scientific, historical or philosophicaltexts, reveal the thought and feeling of a determined human group with respect totheir natural environment, so the epigraphic documents express, in another way,their specific relationship with nature.The present work intends to analyze in some of these documents the way in whichthe ancient Greeks were linked to their natural environment.Along with the linguistic considerations that will certainly arise from the analysisof the inscriptions, we believe that this other point of view, which springs up in generalfrom questions typical of daily life, that they reflect, can be extremely significant.
Keywords: man and nature - inscriptions - linguistic considerations